OUR KNOWLEDGE OF ICE REGIME OF THE KURISCHES HAFF (K Voprosu ob Izuchennosti Ledovogo Rezhima Kurshskogo Zaliva) - Pustovalova,T. V. (1970)
Data gathered by observation stations since 1900 disclose the nature and variations of ice condition in the Kurisches Haff. As a rule, the ice is thicker in the wider central and southern parts of the gulf than in the narrowing northern part of gulf which is more subjected to the influence of the sea. The mean duration of ice is 80 days, minimum 30 days, maximum 3.5-4 months. The ice usually appears at the beginning of December, the mean date being 3 December, the early date 31 October, the late date 21 January. The ice disappears in March, the mean date being 20 March, the early date 6 February, the late date 18 April. (Author) Trans. of Gidrometeorologicheskaya Observatoriya. Trudy (USSR) n1 p182-187 1964, by M. Slessers.